THE EFFECTS OF EXTRACTS OF ATRACTYLODES MACROCEPHALA KOIDZ COMBINED WITH TRANSCUTANEOUS ELECTRICALACUPOINT STIMULATION IN TREATING THE OVARIECTOMIZED FEMALE RATS - Weng, Qing; Cao, Zhu-Feng; Yu, Yan-Wen; Lv, Xiang-Lin; Qu, Fan; Zhou, Jue (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The present study was to explore the effects of the extracts of Atractylodes macrocephala Koidz (EAMK) combinedwith transcutaneous electrical acupoint stimulation (TEAS) on the ovariectomized female rats.Materials and Methods: Forty female Sprague-Dawley rats were randomly divided into four groups: sham-operation, model, livialand EAMK+TEAS groups (n=10 in each group). After the individual treatments for 8 weeks ended, the serum levels of estradiol(E2), follicle stimulating hormone (FSH), luteinizing hormone (LH), osteocalcin and interleukin-6 (IL-6) were measured withcommercial enzyme-linked immunosorbent assay.Results: We found that in the sham-operation group, the serum E2 and osteocalcin levels were significantly higher, and the serumlevels of FSH, LH and IL-6 were markedly lower than those of other groups (P<0.05). No significant differences existed between thelivial and EAMK+TEAS groups on the serum E2 and osteocalcin levels (P>0.05), however, the serum FSH and IL-6 levels ofEAMK+TEAS group were significantly lower than those of the livial group (P<0.05).Conclusion: EAMK combined with TEAS has promises in treating the ovariectomized female rats.